THE REASONABILITY OF BLUEBERRY CONCENTRATED JUICE APPLICATION IN THE MANUFACTURE OF DRY-CURED PORK - Oksana A. Kovaleva; Katherine M. Zdrabova (Теория и практика переработки мяса, 2018)
The aspects of the blueberry concentrated juice application in the production of dried pork as an ingredient of the salt mixture were studied. The organoleptic evaluation of the obtained products using concentrated blueberry juice with different concentrations of solids was carried out. The chemical composition of the finished experimental products is investigated. The influence of the concentrated juice of blueberries to the number of QMAFAnM on the surface of the product (bacteriostatic effect). It is shown that dry-cured pork, injected with a salt mixture with concentrated blueberry juice, has higher taste and aromatic characteristics, improved consistency. In this work, the chemical composition of experimental samples of dry-cured pork is evaluated. It is shown that the use of concentrated blueberry juice in salting increases the moisture content and essential micronutrients. Was found that the number of mesophilic aerobic and facultative-anaerobic microorganisms depends on the amount of dry substances, in particular organic acids, in concentrated blueberry juice, namely, with an increase in the concentration of blueberry juice used in the salt mixture, the amount of QMAFAnM on the surface of the product decreases. Concentrated blueberry juice acts as an inhibitor of growth of pathogenic microflora. On the basis of the conducted researches the optimum content of dry substances for application of the concentrated juice from blueberries at a salting of dry pork is established.